PERSEPSI SISWA TERHADAP PENGGUNAAN GAME EDUKASI DIGITAL PADA PEMBELAJARAN MATEMATIKA - Gegana Bima Hendrawan; Rina Marlina (IKIP Siliwangi, 2022)
This paper examined the students’ view on advantages of using digital educational game in learning mathematics. The background of this paper is the appearance of people perception phenomenon about the negative effect of using games for learning. The method of this paper conducted descriptive qualitative design for the questionnaire and interview as the instruments. The data analysis technique used is the Miles and Huberman model (Analysis Interactive Model). This paper was conducted at Vocational High School for 21 students. The result of data analysis indicated that almost all of the students (86%) agree for using educational game can facilitate the students to learn mathematic. On the other hand, there were only 3 students claimed that the they were not sure or even do not know of using educational game can facilitate the students to learn mathematic. And there were no students who disagree if using educational games can not facilitate the students to learn mathematic.